Recommending Physical Activity to Your Aging Patients? What Clinicians Need to Know to Increase Adherence From the Older Adult Perspective - Cabral, Danylo F.; Santos, Vinicius S.; Silva, Maria Jasmine G.; Leite, Gabriela F.; Mesquita, Ana Paula B.; Pascual-Leone, Alvaro; Cahalin, Lawrence P.; Batiston, Adriane P.; Oliveira, Augusto C. A.; Gomes-Osman, Joyce (Frontiers in Rehabilitation Sciences, 2022)
A wealth of scientific evidence supports that being physically active may prevent or delay the onset of cognitive impairment and dementia. However, a critical barrier is that while most clinicians recommend physical activity (PA) and older adults recognize its health benefits, most older adults fail to regularly practice PA. Thus, it is necessary to explore and disseminate knowledge on how to help clinicians truly partner with people and help them to change their behavior and become more active. Clinical and scientific efforts are underway to establish dose-specific PA recommendations for cognitive brain health. However, an important knowledge gap is how to develop effective strategies to increase PA adherence in aging. To better understand the perspective of older adults, we undertook a mixed-method study on sixty-five sedentary older adults at risk for cognitive decline. Participants answered a questionnaire battery related to PA engagement, and a subcohort participated in a remote focus group. Our findings revealed four main themes: First, age and aging are determinants in PA practice. Second, maintaining both an active mind and autonomy are priorities, but planned PA is not usually related as part of being “active”. Third, motivational challenges in PA engagement were noted. And fourth, they emphasized a call for tailored recommendations. Therefore, we present a multidimensional model of PA adherence to maximize brain health in older adults and suggest a tool kit and key questions to effectively screen sedentary aging adults and translate current guidelines into the needs of the individual by using behavior change strategies.